Increasing non-exercise physical activity : extended theory of planned behaviour model testing and the role of stress within sedentary parents - Loosveldt, Justine (2015)
Although much research has been done in studying physical activity and its health benefits, inactive behaviour has obtained little attention. The main purpose of the present study is to test the Theory of Planned Behaviour (TPB) in predicting sedentary behaviour to a group of parents with young children and a sedentary job. The secondary purpose of this study is to explore if stress explains additional variation when is entered as an additional variable between intention and sedentary behaviour. The sample consisted of 68 sedentary adults with young children, both men (N = 29) and women (N = 39), (M = 37.8 years and SD = 5.8). Participants were divided into two groups: an experimental group who received the intervention and a control group who was not exposed to the intervention but underwent the same measurements. Sedentary behaviour has been assessed with EMG data and calculated to sedentary ratio. Variables of the TPB model (intention, attitude strength, perceived behaviour control , self-identity and perceived knowledge) were assessed by questionnaires. Occupational stress was measured by Heart Rate Variability (HRV) where RMSSD functioned as an indicator for stress. Linear regression analyses indicated that the extended TPB model explained the variance only in the experimental group. Stress has been found to explain larger amount of variation in the control group than in the experimental group. This study shows that the intervention to increase non-exercise physical activity makes people aware of their sedentary behaviour. Also, stress seems to be a factor that interferes between intention and behaviour for sedentary people. Overall, paying attention to diminishing sitting time should be beneficial for public health and increase health outcomes. People need to be aware of the harming effects of their sedentary behaviour and how to increase their non-exercise physical activity in order to be able to make small changes in their everyday routine, ultimately leading to the reception of health benefits elicited from these changes. Moreover, stress management strategies should be included in future interventions, as stress might be seen as a barrier in increasing non-exercise physical activity.